Drawing dragons : learn how to create fantastic fire-breathing dragons - Staple, Sandra (Berkeley, CA : Ulysses Press, 2008)
"In easy-to-follow, step-by-step detail, Drawing Dragons teaches you all the tricks and tecniques you'll need to creat your own amazing dragons"-- P. 4 of cover.
Keywords: Drawing -- Technique -- Juvenile literature; Dragons in art -- Juvenile literature